Escherichia coli expression and purification of LL37 fused to a family III carbohydrate-binding module from Clostridium thermocellum - Ramos, Reinaldo Rodrigues (2010)
[Excerpt] Introduction: LL-37 (LLGDFFRKSKEKIGKEFKRIVQRIKDFLRNLVPRTES) is a very promising human cationic peptide with 37 aminoacids and α-helix structure. It has been shown to exhibit a broad spectrum of antimicrobial activity and to have additional defensive roles such as regulating the inflammatory response and chemo-attracting cells of the adaptative immune system to wound or infection sites, binding and neutralizing lipopolysaccharides (LPS), promoting angiogenesis, reepithelialization and wound closure. [...]